The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1161/strokeaha.116.016563
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor 1 and the Risk of Ischemic Stroke

Abstract: Background Low insulin-like growth factor 1 (IGF-1) have been associated with increased risk of atherosclerosis and atrial fibrillation in cross-sectional studies. Yet, prospective data linking IGF-1 levels to the development of ischemic stroke remain inconclusive. We examined prospectively the association between serum IGF-1 levels and incident ischemic stroke. Methods We measured serum IGF-1 levels in 757 elderly individuals (mean age 79±5, 62% women), free of prevalent stroke, from the Framingham original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 40 publications
(48 reference statements)
2
56
0
2
Order By: Relevance
“…Insulin‐like growth factor 1 (IGF‐1) plays an important role in brain development and normal growth . IGF‐1 reduces the progression of atherosclerosis, and in cross‐sectional studies, low circulating IGF‐1 is associated with increased risk of ischemic stroke . In humans, low levels of IGF‐1 are associated with stroke risk factors such as diabetes, hypertension, and coronary artery disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin‐like growth factor 1 (IGF‐1) plays an important role in brain development and normal growth . IGF‐1 reduces the progression of atherosclerosis, and in cross‐sectional studies, low circulating IGF‐1 is associated with increased risk of ischemic stroke . In humans, low levels of IGF‐1 are associated with stroke risk factors such as diabetes, hypertension, and coronary artery disease .…”
Section: Introductionmentioning
confidence: 99%
“…1 IGF-1 reduces the progression of atherosclerosis, and in cross-sectional studies, low circulating IGF-1 is associated with increased risk of ischemic stroke. 2 In humans, low levels of IGF-1 are associated with stroke risk factors such as diabetes, hypertension, and coronary artery disease. [3][4][5] Previous studies regarding stroke patients have suggested that low IGF-1 levels in the circulation are related with higher stroke severity, poor outcome, and less rates of survival after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of IGF-1 are associated with cardiovascular disease risk. 30, 31 It is known that IGF-1 activates the PI3K/Akt pathway and promotes the synthesis of nitric oxide to prevent cardiovascular disease. 32, 33 Several studies…”
Section: Papp-a Knockdown Suppresses the Production Of Inflammatory Cmentioning
confidence: 99%
“…A case-control study of ischaemic stroke (IS) in a Korean population observed that common variants in IGF1 genes (rs2162679 and rs6214) exhibited protective effects on the development of IS [12]. Epidemiological studies revealed that the levels of circulating IGF1 and IGFBP3 below normal range were associated with the increased morbidity and mortality from ischaemic heart disease and stroke [13][14][15]. In addition, evidence supported that the prevalence of hypertension-induced cerebral haemorrhages and acute ischaemic stroke dramatically increased in people with a declining circulating IGF1 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%